Diagnostic Accuracy of Urine Dipstick for Proteinuria in Pre-Eclampsia - ASMA YASEEN, RAKHSHANDA REHMAN, AFSHAN USMANI, NUZHAT MALIK (Journal of Fatima Jinnah Medical University, 2018)
OBJECTIVE: To evaluate the diagnostic accuracy of dipstick urine analysis in single voided urine by using quantification of urinary proteins in 24 hours collection as gold standard in pre-eclamptic patients. STUDY DESIGN: Cross sectional survey. PLACE AND DURATION OF STUDY: This study was conducted in Obstetrics and Gynaecology Unit-I, Sir Ganga Ram Hospital, Lahore,during the period of six months from February 2009 to July 2009. SUBJECTS & METHODS: Two hundred and twenty five cases of preeclampsia were included in this study and were clinically examined in Out-patient and Emergency Departments. In all these patients urinary protein was assessed by researcher using urine dipstick in (+2 or more) single voided urine as well as in 24 hours urinary collection (gm/24 hours) which was analyzed in laboratory of Sir Ganga Ram Hospital, Lahore. The results of both techniques were compared in all patients. RESULTS: The mean standard deviation was 25.78±3.94 years. Twenty four hour urine is the gold standard for the evaluation of proteinuria with a sensitivity of 82% for pre-eclampsia patients, specificity had 62%, the positive predictive value was 77%, negative predictive value was 69% and accuracy rate was 73.78% The values for the 24-hour for patients with urinary protein. CONCLUSION: All women with hypertension during pregnancy should have a 24 hour urine protein measurement. There may be a role in doing 6 or 12 hour urine collections to screen for proteinuria. Therefore, current practice at the labouratory should change to doing 24 hour urinary protein measurements on all hypertensive pregnant women.